Impact of Weight Loss Strategies on Obesity‐Induced DNA Damage. Issue 17 (14th June 2019) - Setayesh, Tahereh; Mišík, Miroslav; Langie, Sabine A. S.; Godschalk, Roger; Waldherr, Monika; Bauer, Thomas; Leitner, Sabine; Bichler, Christoph; Prager, Gerhard; Krupitza, Georg; Haslberger, Alexander; Knasmüller, Siegfried
Abstract : Scope: Obesity causes DNA damage, which is causally related to several disorders including cancer, infertility, and cognitive dysfunctions. The aim of this study is to investigate whether weight loss improves the integrity of the genetic material. Methods and Results: Overweight mice are fed ad libitum either with a Western diet (WD), with a 40% caloric restricted WD, or with a high carbohydrate low protein (HCLP) diet. Caloric restriction and also the HCLP diet lead to ca. 30% weight loss, which is paralleled by decreased DNA damage ("comet" formation) and oxidative damage of purines in inner organs, additionally the activity of nucleotide excision repair increased. The effects are more pronounced in animals that have received the HCLP chow. Results of biochemical analyses indicate that the reduction of DNA damage is associated with a decrease of pro‐inflammatory cytokines and lower insulin levels. Conclusion: The study indicates that weight loss may prevent obesity‐associated adverse health effects due to reduction of overall DNA damage. Abstract : Weight loss of overweight mice via reduced consumption of a high‐fat Western diet or by a high‐carbohydrate diet leads to reduced DNA damage, decreased formation of oxidized purines in several inner organs, and additionally causes an increase of the activity of nucleotide excision repair. These processes may be causally related to a decline of the levels of pro‐inflammatory cytokines and reduction of the insulin concentrations in the blood, which are observed after the weight loss.